The 2015 Nepal Gorkha Earthquake: An overview of the damage, lessons learned and challenges - H. Hazarika; N.P. Bhandary; Y. Kajita; K. Kasama; K. Tsukahara; R.K. Pokharel (International Association of Lowland Technology, 2016)
This paper describes the damage brought by the 2015 Nepal earthquake to urban infrastructures, modern and traditional buildings as well as some word heritage sites in and around Kathmandu city. The paper also focuses on a disaster brought to a hydropower plant by the compound action of a previous landslide and this time earthquake. Some of the possible reasons for such damage were brought to light, and challenges of the geotechnical community towards the retrofitting and recovery of the devastated structures were discussed